Implementasi Pembelajaran Melalui Media Whatshapp Group Ditinjau Dari Motivasi Belajar Mahasiswa (Masa Pandemic Covid 19) - Sriyanti Sriyanti; Ayu Munawaroh; Karliana Indrawari (STAI Bumi Silampari, 2021)
This research is a field research (field research) aims to determine the implementation of Whatshap Group Media in the learning process in the PAI UM Palembang Study Program, student learning motivation after being applied by the Whatshap Group Media in the PAI UM Palembang Study Program during the Covid 19 pandemic, and to see the advantages and lack of application of Whatshap Group Media in learning in increasing learning motivation in the PAI UM Palembang Study Program. The method used is a qualitative descriptive method. Data collection techniques using observation, questionnaires, interviews, and documentation. Data analysis techniques with data collection steps, data reduction, data presentation and conclusions. The results of the study were the Covid 19 pandemic period of student learning at the Palembang UM Campus, especially the PAI study program, experienced a change from face-to-face learning to online learning. Online learning requires lecturers to use technology more in learning and requires students to be more independent in the learning process. In online learning, lecturers use a lot of technological learning media, namely whatshap media, zoom meetings, google classroom. Learning with whatshap group media has a good effect on learning motivation, results, and understanding if there is collaboration with other media such as zoom, google met or google class room, because so far students learn face-to-face, directly seeing the lecturer explain. When discussing there is a reciprocal response between lecturers and students. But for some lecturers, some students are not very active in the learning process if they only use whatshap media, students are only as readers but not as implementers. Online learning carried out using the WhatsApp group application has advantages and disadvantages.